Multifunctional exosomes derived from bone marrow stem cells for fulfilled osseointegration - Zhuang, Jingwen; Hang, Ruiyue; Sun, Ruoyue; Ding, Yanshu; Yao, Xiaohong; Hang, Ruiqiang; Sun, Hui; Bai, Long (Frontiers in Chemistry, 2022)
Bone marrow mesenchymal stem cells (BMSCs) have self-renewal, multi-directional differentiation potential, and immune regulation function and are widely used for de novo bone formation. However, the wide variation in individual amplification, the potential risk of cancer cell contamination, and the need for culture time significantly limit their widespread use clinically. Alternatively, numerous studies have shown that exosomes secreted by BMSCs in the nanoscale can also affect the functionality of endothelial cells (angiogenesis), macrophages (immunomodulation), and osteoblasts/osteoclasts (osteogenesis), which is a highly promising therapy for osseointegration with pronounced advantages (e.g., safety, high efficiency, and no ethical restrictions). The review aims to summarize the multifaceted effect of BMSCs-derived exosomes on osseointegration and provide reference and basis for rapid and qualified osseointegration.